The Religious Values of Congklak as the Basis for Character Education Strategies in Elementary Schools - Fajar Nugraha; Cece Rakhmat; Sofyan Sauri; Encep Syarief Nurdin (Papanda Publisher, 2026)
The limited integration of traditional games as systematic strategies for religious character education in elementary schools indicates a gap between local cultural heritage potential and classroom practices. Congklak, though familiar to Indonesian children, has rarely been examined as a medium for embedding religious values within character education strategies. This study identifies religious values embedded in congklak and examines their relevance as foundations for developing religious character education strategies in elementary schools. A descriptive qualitative approach was employed, with data collected through semi-structured in-depth interviews with an academic expert and cultural practitioner, complemented by literature review. Thematic analysis identified recurring values, which were triangulated across sources to ensure credibility. Five core religious values were identified: honesty (moving seeds accurately without supervision), patience (turn-taking and accepting outcomes), empathy (comforting peers), sportsmanship (accepting victory and defeat with humility), and gratitude (acknowledging outcomes). These values emerge naturally through game mechanics and player interactions rather than explicit instruction. Congklak functions as a culturally grounded, experiential medium for internalizing religious values. When integrated into curriculum with guided reflection, it offers elementary teachers a contextual, engaging pedagogical strategy for religious character development. Future research should examine classroom implementation effectiveness through empirical longitudinal studies.